2020
DOI: 10.1126/sciadv.aaz6997
|View full text |Cite
|
Sign up to set email alerts
|

Cellular contractile forces are nonmechanosensitive

Abstract: Cells’ ability to apply contractile forces to their environment and to sense its mechanical properties (e.g., rigidity) are among their most fundamental features. Yet, the interrelations between contractility and mechanosensing, in particular, whether contractile force generation depends on mechanosensing, are not understood. We use theory and extensive experiments to study the time evolution of cellular contractile forces and show that they are generated by time-dependent actomyosin contractile displacements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…In agreement with this hypothesis, vinculin regulates cell elongation on glass substrates ( Ezzel et al., 1997 ). Although observations in fibroblasts suggest that traction forces are independent of ECM stiffness ( Feld et al., 2020 ; Freyman et al., 2002 ), as we assumed in this model, there are also contradicting observations: (1) vinculin increases cell traction forces ( Dumbauld et al, 2013 ), and (2) stressing FAs induces -smooth muscle actin recruitment to stress fibers, which in turn increases traction forces ( Goffin et al, 2006 ). We have, therefore, also tested an alternative mechanism in which planar stress induces an increase in cell traction forces ( Figure S3 ); this mechanism also suffices for cell elongation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In agreement with this hypothesis, vinculin regulates cell elongation on glass substrates ( Ezzel et al., 1997 ). Although observations in fibroblasts suggest that traction forces are independent of ECM stiffness ( Feld et al., 2020 ; Freyman et al., 2002 ), as we assumed in this model, there are also contradicting observations: (1) vinculin increases cell traction forces ( Dumbauld et al, 2013 ), and (2) stressing FAs induces -smooth muscle actin recruitment to stress fibers, which in turn increases traction forces ( Goffin et al, 2006 ). We have, therefore, also tested an alternative mechanism in which planar stress induces an increase in cell traction forces ( Figure S3 ); this mechanism also suffices for cell elongation.…”
Section: Discussionmentioning
confidence: 69%
“…In many models, it is assumed that cells become more contractile on stiffer substrates. However, it has been shown in fibroblasts that contractile forces do not depend on substrate stiffness ( Feld et al., 2020 ; Freyman et al., 2002 ). Here we show that mechanosensitive focal-adhesion turnover, together with cell contractility and substrate adhesion suffice to explain all three ECM-stiffness-dependent cell behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-pillar setup, in which cells are cultured on pillar-array of defined length and stiffness, is a well-established platform to study cell-matrix interaction [ 64 , 65 ]. Wolfenson et al have shown that actomyosin-based contractile units activity between sub-micron pillars involves nanometer-scale rhythmic steps [ 23 ], and that long-term force application on micropillars is driven by local fluctuations in actin density [ 55 ]. As another demonstration of our tool’s capability, we have analyzed videos of MDA-MB-231 cells grown on top of micropillars.…”
Section: Resultsmentioning
confidence: 99%
“…The following day, cells were trypsinized using TrypLE (Biological Industries), centrifuged with growth medium, and then resuspended and pre-incubated in in HBSS buffer supplemented with 20 mM Hepes for 30 min before the experiment. Cells were then plated on top of the micropillars substrate, as previously reported by Wolfenson et al [ 23 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation